Energy Storage: Lattice‐Cell Orientation Disorder in Complex Spinel Oxides (Adv. Energy Mater. 4/2017). Issue 4 (February 2017) - Chen, Yan; Cheng, Yongqiang; Li, Juchuan; Feygenson, Mikhail; Heller, William T.; Liang, Chengdu; An, Ke
Abstract : Transition metal arrangement impacts electrochemical behaviors of high‐voltage electrodes for Li‐ion batteries. In article number 1601950, Ke An and co‐workers report a new lattice‐cell orientation disorder model as the local ordering mechanism, which explains the difference between global and local structures of LiNi0.5 Mn1.5 O4 . The cover picture shows an arrangement of the unit cells by color with different orientations.